2017
DOI: 10.1186/s13037-017-0143-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hepatic failure with a new diagnostic technique by preoperative liver scintigraphy and computed tomography: a pilot study in 123 patients undergoing liver resection

Abstract: BackgroundA novel index, total liver LU15, has been identified as a surrogate marker for liver function. We evaluated the ability of preoperative remnant liver LU15 values to predict postoperative hepatic failure.MethodsPreoperative risk factors for postoperative hepatic failure and remnant liver LU15 were evaluated in 123 patients undergoing liver resection for several diseases from September 1st, 2007 to December 1st, 2016. We calculated the remnant liver LU15 value from the total liver LU15 value and the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The indication of hepatectomy for liver metastasis was good function of future remnant liver and without extrahepatic lesions. And the PVE indication was less than 13.0 of remnant liver LU calculated by 99 m-Tc-GSA liver scintigrahy [ 6 ]. ALLPS procedure was performed with only the patients, who has insufficient future remnant liver volume and whom was planned surgical procedure of tri-sectionectomy and partial hepatectomy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The indication of hepatectomy for liver metastasis was good function of future remnant liver and without extrahepatic lesions. And the PVE indication was less than 13.0 of remnant liver LU calculated by 99 m-Tc-GSA liver scintigrahy [ 6 ]. ALLPS procedure was performed with only the patients, who has insufficient future remnant liver volume and whom was planned surgical procedure of tri-sectionectomy and partial hepatectomy.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the distribution of 99mTc-GSA in the liver is not dependent on liver blood flow [ 5 ]. Our previous study has shown that a novel index, remnant liver LU15, has been identified as a surrogate marker for remnant liver function and preoperative remnant liver LU15 values might predict hepatic failure following a liver resection without biliary reconstruction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the usefulness of Tc-99m galactosyl human serum albumin (GSA) scintigraphy for more accurate evaluation of underlying liver diseases, such as cirrhosis [4,5], during both the preoperative [2,3,6] and peri-PTPE period [7,8], have been reported. A variety of radionuclide parameters can be used for Tc-99m GSA scintigraphy, depending on the institute.…”
Section: Introductionmentioning
confidence: 99%
“…Residual liver uptake at 15 minutes (RLU15), which was reported by Koizumi et al ., is the cumulative residual liver accumulation rate of a GSA tracer 15 minutes after its injection, and it indicates residual liver function [9]. To safely perform hepatectomies, it has been reported that the RLU15 should theoretically [10] and clinically [2] be 13 or more. A co-author of the present manuscript has already reported the usefulness of using RLU15 to predict liver failure [2]; however, to date, there has been no evaluation of the effectiveness of PTPE using RLU15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation